2014
DOI: 10.1371/journal.ppat.1004469
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling Human Trypanotolerance: IL8 is Associated with Infection Control whereas IL10 and TNFα Are Associated with Subsequent Disease Development

Abstract: In West Africa, Trypanosoma brucei gambiense, causing human African trypanosomiasis (HAT), is associated with a great diversity of infection outcomes. In addition to patients who can be diagnosed in the early hemolymphatic phase (stage 1) or meningoencephalitic phase (stage 2), a number of individuals can mount long-lasting specific serological responses while the results of microscopic investigations are negative (SERO TL+). Evidence is now increasing to indicate that these are asymptomatic subjects with low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 43 publications
1
37
0
Order By: Relevance
“…This module provided compelling evidence for inflammatory transcript enrichment in T cells during breakthrough acute disease, including the following inflammatory transcripts from the "Zhou_Inflammatory_response_FIMA_Up" gene set 44 : IL8, CCL20, CXCL3, CXCL1, PTX3, IL1b, IER3, CRISP3, G0S2, TLR2, PTGS2, CXCL2 (highlighted in Figure 6D black box), the first 6 of which have been linked to Th/Tc17-mediated inflammation in both preclinical models and in human disease. 45,46 The black module was also enriched for multiple other pathways of immune activation, including the KEGG and reactome "asthma," "signaling in the immune system," "GVHD" pathways as well as the KEGG "cytokine:cytokine receptor interaction" and "chemokine signaling" pathways ( Figure 6F; supplemental Table 8). …”
Section: -21mentioning
confidence: 99%
“…This module provided compelling evidence for inflammatory transcript enrichment in T cells during breakthrough acute disease, including the following inflammatory transcripts from the "Zhou_Inflammatory_response_FIMA_Up" gene set 44 : IL8, CCL20, CXCL3, CXCL1, PTX3, IL1b, IER3, CRISP3, G0S2, TLR2, PTGS2, CXCL2 (highlighted in Figure 6D black box), the first 6 of which have been linked to Th/Tc17-mediated inflammation in both preclinical models and in human disease. 45,46 The black module was also enriched for multiple other pathways of immune activation, including the KEGG and reactome "asthma," "signaling in the immune system," "GVHD" pathways as well as the KEGG "cytokine:cytokine receptor interaction" and "chemokine signaling" pathways ( Figure 6F; supplemental Table 8). …”
Section: -21mentioning
confidence: 99%
“…For example, trypanotolerant patients have been characterized as having a marked inflammatory response with elevated levels of plasmatic IL8, IL6 and TNF‐α. For these patients, increase in IL‐10 levels and decrease in TNF‐α levels were markers of disease development during follow‐up . IL‐10 has been found to be essential for maintenance of the immunological balance between protective and pathological immune responses during HAT.…”
Section: Discussionmentioning
confidence: 97%
“…For these patients, increase in IL-10 levels and decrease in TNF-α levels were markers of disease development during follow-up. 29 IL-10 has been found to be essential for maintenance of the immunological balance between protective and pathological immune responses during HAT. It has been recently shown that other pathways may also contribute to maintain this immunological balance, such as IL-27 signalling.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in HAT caused by the gambiense strain (considered as invariably fatal), cases of self-cure in untreated patients have been described, although accurate diagnostic tools were not available at the time (revised by Jamonneau et al, 2012). In studies performed in mangrove areas of coastal Guinea, high levels of IL-10 and low levels of TNF-α have been associated with an increased risk to suffer HAT, whereas high levels of IL-8 were associated with disease control (Ilboudo et al, 2014). Recent data from patients that refused to receive chemotherapy and were monitored for periods from 5 to 15 years demonstrated parasite clearance, as observed using follow-up tools such as microscopy and polymerase chain reaction.…”
Section: Parasite-human Host Interactionmentioning
confidence: 99%